Development of Learning Media Based on Car Racing Games In Mandarin Subjects For Class X Pangudi Luhur Don Bosko High School Semarang - Anggi Novita Sari Prasetyo; Anggraeni Anggraeni; Rina Supriatnaningsih; Sheyra Silvia Siregar (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2023)
By promoting fun and exciting learning, researchers develop a product that can be used in the teaching and learning process with a view to increasing the learning motivation of all students in learning and assisting eduacators in making it easier for an educator to deliver lessons. The purpose of this study is  1) to describe the result of the analysis of the needs of students and teacher on the development of car racing game media in Mandarin class in X class at Pangudi Luhur Don Bosko high school 2) to describe the prototype of the development of car racing game media in X class at Pangudi Luhur Don Bosko high school 3) to describe the result of expert validation on the development of car racing game media in X class at Pangudi Luhur Don Bosko high school developed by researchers.   The study uses research and development methods with five stages, namely 1. Potential problems, 2. Data collection, 3. Product design, 4. Product validation, 5. Product revision.  From the results of the analysis of interviews with subject teachers and analysis of needs questionnaires  student agree with development of  game- based learning media that are creative, effective and fun.  The validation result show that the car racing game-based learning media gets an average score of 87 from media expert and 87,5 from material expert, both of which show a score of 4 which means the media is very feasible to use. The media is then corrected according to suggestions and input from expert.